Mineral nutrition of papaya trees (Carica papaya L.): V. nutrient uptake under field conditions - Cunha, Rubens José Pietsch; Haag, Henrique Paulo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
The present research was set out under field conditions in Botucatu county, São Paulo, Brazil, with a Cf.b. type of climate and a Paleudalf soil. The purpose was to study N, P, K.. Ca, Mg, S, B, Cu, Fe, Mn, Mo, and Zn uptake by the plants. Collected data showed that nutrient uptake increased during first year of growth, reaching its maximum in the 12 th month. During the first year growth, the nutrient uptake by the aerial parts of plant had the following order: N 66.7g; K - 62.8g; Ca - 24.8g; Mg - 10.3g; S - 7.3g; P-6,3g; Fe - 229.8mg; Mn - 149.lmg; Zn - 79.7mg; B - 74.2mg; Cu-20.0 mg; Mo - 0.15mg.